Boosting electrochemical nitrite–ammonia conversion properties by a Cu foam@Cu2O catalyst. Issue 4 (15th December 2021) - Chen, Qiuyue; An, Xuguang; Liu, Qian; Wu, Xiaoqiang; Xie, Lisi; Zhang, Jing; Yao, Weitang; Hamdy, Mohamed S.; Kong, Qingquan; Sun, Xuping
Abstract : CF@Cu2 O is a superb NO2 − reduction reaction electrocatalyst, achieving high-efficiency electrosynthesis of ammonia from nitrite with an excellent ammonia yield of 7510.73 μg h − 1 cm − 2 and Faraday efficiency of 94.21%. Abstract : Electrocatalytic reduction of nitrite (NO2 − ) to ammonia (NH3 ) can simultaneously achieve wastewater treatment and ammonia production, but it needs efficient catalysts. Herein, Cu2 O particles self-supported on Cu foam with enriched oxygen vacancies are developed to enable selective NO2 − reduction to NH3, exhibiting a maximum NH3 yield rate of 7510.73 μg h −1 cm −2 and high faradaic efficiency of 94.21% at − 0.6 V in 0.1 M PBS containing 0.1 M NaNO2 . Density functional theory calculations reveal the vital role of oxygen vacancies during the nitrite reduction process, as well as the reaction mechanisms and the potential limiting step involved. This work provides a new avenue to the rational design of Cu-based catalysts for NH3 electrosynthesis.